The presidency - Cohen, Jeffrey (McGraw-Hill / Irwin, 2003)
The Presidency: Classic and Contemporary Readings covers a wide range of time, approaches, characters, ideas, and perspectives. From Alexander Hamilton's Federalist Papers to recent journalistic reactions of President George W. Bush's speech directly following the September 11th attacks, the editors of this volume strive to cover all facets of the person and the office.